If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X(X-5)*2=(2X+1)(2X+1)-(4X-13)
We move all terms to the left:
X(X-5)*2-((2X+1)(2X+1)-(4X-13))=0
We multiply parentheses
2X^2-10X-((2X+1)(2X+1)-(4X-13))=0
We multiply parentheses ..
2X^2-((+4X^2+2X+2X+1)-(4X-13))-10X=0
We calculate terms in parentheses: -((+4X^2+2X+2X+1)-(4X-13)), so:We add all the numbers together, and all the variables
(+4X^2+2X+2X+1)-(4X-13)
We get rid of parentheses
4X^2+2X+2X-4X+1+13
We add all the numbers together, and all the variables
4X^2+14
Back to the equation:
-(4X^2+14)
2X^2-10X-(4X^2+14)=0
We get rid of parentheses
2X^2-4X^2-10X-14=0
We add all the numbers together, and all the variables
-2X^2-10X-14=0
a = -2; b = -10; c = -14;
Δ = b2-4ac
Δ = -102-4·(-2)·(-14)
Δ = -12
Delta is less than zero, so there is no solution for the equation
| m+7=22m= | | 7x+18=207 | | (2a+5)*(2a+5)=(2a+5)(2a-5) | | 3a-1/4=2a+5 | | 34-12x=28x=36 | | x+15+11=70 | | 10v^2+40v+50=0 | | -13+2x=4x-9 | | -7+11p=3p-37 | | 5x-2÷3=4x+1÷2 | | 4-6n=60+2n | | 4x+12=8x–4 | | -27=-3(x-1)(x-3) | | 1/80x=1/10 | | 16−5y=6 | | 16−5y/3=2 | | –27.09=3.87a | | 4x–3=x+3 | | −11x+26−(−4)=6x | | 2x+6+1-3=12 | | (2x+4)+x=180 | | 2a/3-4=a-7 | | (3x-24)=(x-10) | | 2(3x+4=) | | 4/2=2x-4 | | 27y*y=1 | | 35x+10=20x-175 | | 7/x=15/1 | | 55(x+3)=7x+5 | | 2=(3x+4) | | 6x+72=4x+28 | | 9/h=1 |